POGO Travel Journal: Pediatric Orthopaedic Service Trip to Portoviejo, Ecuador : Invited Perspective - Rambo, Anna; Justin Badon; Murphy Walters; Khristinn Kellie Leitch (Journal of the Pediatric Orthopaedic Society of North America, 2023)
This travel report shares the perspective and experience of an early career pediatric orthopaedic surgeon on an global outreach trip to Portoviejo, Ecuador. She shares the importance of community outreach, teamwork, and decision-making in an international setting. Providing education to a local team of surgeons, surgical techs, and clinical staff as well was a unique educational and cultural experience for residents from North America are the focal points of her experience. Typical patients and cases included children with developmental dysplasia of the hip, clubfoot, trauma, upper and lower extremity deformities, and children with neuromuscular orthopaedic issues.